1996
DOI: 10.2337/diab.45.9.1229
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Linkage of Obesity and Energy Metabolism to Markers Flanking Homologues of Rodent Obesity Genes in Pima Indians

Abstract: The homologues of single genes that cause obesity in rodents are suggested as candidate genes for modulation of body composition in humans. Among these genes are the four mouse mutations-diabetes (db), obesity (ob), tubby (tub), and yellow agouti (Ay). Variation in the human counterparts to these genes (OB, DB, TUB, and ASP, respectively) may contribute to human obesity, which is thought to have a substantial genetic component. To initially assess the potential contribution of these genes to human obesity, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 0 publications
0
33
0
1
Order By: Relevance
“…The contributions of the leptin-receptor polymorphisms Lys109Arg, Gln223Arg, and Lys656Asn on obesity were analyzed (36). On the other hand, other investigators have observed no linkages between leptin-receptor polymorphisms and obesity in Pima Indians (37) and in French subjects (38). The contributions of leptin-receptor polymorphisms to obesity are thus controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The contributions of the leptin-receptor polymorphisms Lys109Arg, Gln223Arg, and Lys656Asn on obesity were analyzed (36). On the other hand, other investigators have observed no linkages between leptin-receptor polymorphisms and obesity in Pima Indians (37) and in French subjects (38). The contributions of leptin-receptor polymorphisms to obesity are thus controversial.…”
Section: Discussionmentioning
confidence: 99%
“…46 At the genetic level, the leptin receptor and acute insulin response loci appear to be closely co-localised on chromosome 1, as demonstrated in Pima Indians. 47 It has been suggested therefore, that the leptin receptor gene could play a secondary role in regulation of the acute insulin response (AIR), with high leptin levels down-regulating the receptor gene and diminishing AIR, which may in turn have implications for insulinaemia and insulin sensitivity. However, if leptin and insulin are acting as part of a feed-back loop controlling adipose tissue mass, each could modulate the other simultaneously.…”
Section: Leptin and Insulin Sensitivity Pz Zimmet Et Almentioning
confidence: 99%
“…28 Polymorphisms in the fatty acid synthase (FAS) gene were shown to be associated with substrate oxidation rates in nondiabetic Pima Indians. 29 No significant linkages were found between traits of resting metabolic rate, 24-h TEE, and 24-h RQ and the diabetes (DB), obesity (OB), tubby (TUB) and yellow agouti (ASP) 30 genes.…”
Section: Discussionmentioning
confidence: 99%